Sexual interactions between adult males and immature females in the subsocial spider Anelosimus vierae - Rojas-Buffet, Carolina; Viera, Carmen (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
This study aimed to analyze the consequences of sexual interactions between adult males and penultimate females of the Uruguayan subsocial spider Anelosimus vierae Agnarsson, 2012 (Theridiidae). In the laboratory, several experimental groups were formed consisting of unrelated adult males and penultimate females of the species. The courtship and pseudo-copulation behaviors that occur between adult males and penultimate females were described in detail. These sexual behaviors were shown to have positive effects on future sexual encounters.
Keywords: Courtship; Pseudo-copula; Subadult females; Communal spider; Uruguayan spider